Geomagnetic response of solar wind-magnetosphere coupling - Singh, A. K. (Indian Institute of Geomagnetism, Mumbai, 2012)
A brief summary of the important new findings is given below: • The data adaptive filtering technique singular spectrum analysis identifies and extracts trend and period modes of around 27-day, 13-day and 9-day in various solar wind and geomagnetic parameters. The response of the magnetosphere to the solar wind forcing is found to be the most prominent during the declining phases of the solar cycles. However, oscillations of these modes have considerable amplitudes during the entire sunspot cycle.Multi-frequency structures in substorm associated magnetic fluctuations are extracted by the SSA. The study throws light on several features of various modes thus detected, for example, poleward propagation of modes at high latitudes, dip equatorial enhancement. • Geomagnetic substorms, which may have considerably high magnetic disturbance (up to ∼-500 nT) at stations poleward of standard auroral oval, are occasionally missed out in the standard AE indices. However, their low latitude signatures like positive bays, Pi2 bursts are often evident. Signature and strength of such substorms have significant asymmetry in the opposite hemispheres. • This study clearly brings out 24-hour periodicity in the ring current asymmetry during magnetic storms. The asymmetry is observed maximum near dusk hours, whereas it is minimum near dawn hours. This periodicity is attributed to changing local time due to rotation of the Earth. For the first time, we also report clear westward and eastward propagating modes around the globe using ground-based magnetic data. These propagation characteristics are associated with the westward and eastward drifts of energetic ions and electrons, respectively in the ring current region. • This thesis reports various new aspects of substorm associated auroral and low latitude indices. (1) The AU index (supposedly positive), which is expected to represent the maximum intensity of the eastward electrojet during a substorm, turns negative under the conditions when entire auroral oval is dominated by westward electrojet. Such negative AU values result in underestimation of strength of substorm in the AE index (AE = AU − AL). Our study supports the finding of Kamide and Ros toker [2004] that use of AE index should be avoided for identification of a substorm.Rather AL index gives better representation of substorms. (2) Intense and prolonged solar flares generate asymmetric magnetic field at low latitudes. This asymmetry significantly alters non-substorm and substorm time ASY indices. (3) Low latitude ASY indices, often used in relation to substorm activities, are affected by prompt penetration of interplanetary electric field to lower latitudes.
A thesis submitted to the university of Mumbai for the Ph. D.(Science) degree in Physics under the guidance of Prof. B.M.Pathan.
Keywords: Geomagnetic activities; Solar wind-magnetosphere coupling; Singular spectrum analysis; Coronal mass ejection; Geomagnetic activities; Geomagnetic storm; ULF waves; Magnetic field; PhD Thesis